Treatment of ethanolamine using an Fe(III)‐based, two‐chamber microbial fuel cell with continuous Fe(II) oxidation at the air cathode. Issue 5 (26th June 2015) - Seo, Seok‐Ju; Shin, Ja‐Won; Maitlo, Hubdar Ali; Park, Joo‐Yang
Abstract: BACKGROUND: The objective of this study was to investigate the feasibility of developing an integrated bio‐electrochemical system for the removal of ethanolamine from wastewater by combining an Fe(III)‐based microbial fuel cell (MFC) with a continuous Fe(II) oxidation system for simultaneous oxidation and reduction of iron in the same compartment. The ethanolamine in the Fe(III)‐based MFC can be effectively converted to electrical energy by using the catalytic activity of microorganisms. In this respect, the authors investigated whether the introduction of a system for Fe(III) regeneration could enhance the sustainability of both power generation and the removal of ethanolamine in this integrated system. RESULTS: The experimental results obtained with a traditional Fe(III)‐based MFC, operated with a ferric sulfate solution of 25 or 50 mmol L −1 Fe(III) mixed with ethylenediaminetetraacetic acid (EDTA) solution of 10 mmol L −1, showed that increasing the Fe(III) concentration leads to improved performance of the MFC; the maximum power density, open circle voltage (OCV), and Coulombic efficiency (CE) were all improved. However, the effluents from the cathode chamber contained a low concentration of Fe(III) due to deficient regeneration of Fe(III). In the integrated bio‐electrochemical system developed in this work (enhanced Fe(III)‐based MFC), the generated Fe(II) was oxidized at the air cathode via favorable oxygen diffusion and a Fe(II)‐based fuel cell (FC). CONCLUSION: Electricity was sustainably generated from the enhanced MFC with 25 mmol L −1 Fe(III); the highest performance, in terms of maximum power density, OCV and CE, was achieved using 50 mmol L −1 Fe(III), thus indicating the increased efficiency of this integrated system. © 2015 Society of Chemical Industry